Politico-Legal Review of the Revised-Bill of the Corruption Eradication Commission and Omnibus Law - JM Muslimin; Novita Akria Putri (Jurnal Media Hukum, 2021)
The paper aims to prove that political compromise may create legal antagonisms, paradoxes and strengthen the influence of elite-oligarchy. The paper is based on the theory that the concept of consensus in the context of the political system is closely related to the Indonesian cultural democracy. However, in the implementation, there is an underlying principle of checks and balances as a systemic guarantee, so that democracy is not merely a tool of ‘killing ground of freedom’ to manipulate the essence of democracy itself, in particular, by the dominant forces of the elite and the oligarchy. Through the socio-historical method (empirical approach), this paper examined the emergence of the phenomenon of antagonism and paradox of regulatory formulation, such as the revision of the Bill for Eradicating Corruption which weakens anti-corruption institutions, Corruption Eradication Commission, to the creation of Omnibus Law, which is considered to make labors structurally marginalized. The investigation discovered that those legal products are distorted and should be originally created to achieve the benefit and interest of society at large. In contrast, they are falsified and manipulated under the banner of ‘consensus’ democracy steered by the limited elite-oligarchy of the Political Parties.